Sakral dan Profan dalam Ritual Life Cycle : Memperbincangkan Fungsionalisme Emile Durkheim - Asliah Zainal (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2014)
AbstractIn various societies, ritual manifest in almost all stages of humanlife. It starts from the conception period; birth, childhood,marriage, death, even after the man was die. With the ritual, peopletry to bring the world and at the same time separate the sacred andthe profane one. This paper shall discuss the life cycle rituals insociety in Emile Durkheim’s theory of functionalism. In Durkheim’spoint of view, society has two sides in their life; time to work andtime celebrate the sacred ritual. The dualism of life is whatDurkheim called "The sacred" and "The profane". Durkheimconsiders The Sacred is everything a superior, powerful, and in thenormal circumstances, it untouched and honored. Instead of theprofane is part of everyday life and mundane. Although the functionof ritual is to approach the sacred One, there are social functionswithin. Therefore, it has the social value in the sense it couldstrengthen social solidarity among community members. Life cyclerituals provide facilities for every person to feel the religiousemotion and feel the presence of the Sacred. Ritual in somecultures, not only a religious obligation but also running efforts toachieve social cohesion as part of a community in which he lives.Keywords: Ritual Life-cycle, Sacred and Profane, EmileDurkheim, Funcsionalism